Evaluation of cellular and molecular impact of zearalenone and Escherichia coli co-exposure on IPEC-1 cells using microarray technology. (December 2016) - Braicu, Cornelia; Selicean, Sonia; Cojocneanu-Petric, Roxana; Lajos, Raduly; Balacescu, Ovidiu; Taranu, Ionelia; Marin, Daniela; Motiu, Monica; Jurj, Ancuta; Achimas-Cadariu, Patriciu; Berindan-Neagoe, Ioana
Abstract Background The gastrointestinal tract is the primary site of toxin interaction, an interface between the organism and its surroundings. In this study, we assessed the alteration of intestinal mRNA profile in the case of co-occurrence of zearalenone (ZEA), a secondaryFusarium metabolite, andEscherichia coli (E. coli), on the intestinal porcine epithelial cells IPEC-1. We chose this model since the pig is a species which is susceptible to pathogen and mycotoxin co-exposure. Results After treating the cells with the two contaminants, either separately or in combination, the differential gene expression between groups was assessed, using the microarray technology. Data analysis identified 1691 upregulated and 797 downregulated genes as a response toE. coli exposure, while for ZEA treated cells, 303 genes were upregulated and 49 downregulated. The co-contamination led to 991 upregulated and 800 downregulated genes. The altered gene expression pattern was further classified into 8 functional groups. In the case of co-exposure to ZEA andE.coli, a clear increase of proinflammatory mechanisms. Conclusions These results demonstrate the complex effect of single or multiple contaminants exposure at cellular and molecular level, with significant implications that might lead to the activation of pathological mechanisms. A better understanding of the effects of co-contamination is mandatory in developing novel exposure regulations and prevention measures.